Managing the technical professional - Kindler, Herbert S. (Crisp Pub. Menlo ParkUS, 1993)
Introduces models, strategies and techniques needed by managers for equipping technical professionals to achieve outstanding performances, and acquire managerial skills. Topics addressed include: understanding what technical professionals want from their management; designing mission, structure, staffing; criteria of outstanding decisions; and, designing the action plan.